PERHITUNGAN CARBON FOOTPRINT DAN COST REDUCTION PADA PEMASANGAN PLTS ATAP ON-GRID 120 kWP : STUDI KASUS DI DINAS KEHUTANAN PROVINSI KALIMANTAN TIMUR - Darmana Tasdik; Elok Faizatul Hikmah; Ariman Ariman (AGUSPATI Research Institute, 2022)
This study was conducted to calculate how much efficiency is produced in the installation of on-grid solar power plants in the Forestry Service of the Samarinda Regency Government and how the impact on reducing carbon gas emissions as an effort to maintain air quality in reducing the greenhouse effect. The research was conducted using a quantitative approach by collecting data in the form of the use of electronic equipment, the number of official vehicles used. Carbon footprint can be calculated in Building A and Building B. Cost Reduction calculation is carried out using PLN electricity usage bill data. The result of the Carbon Footprint calculation was obtained at 1234.41 Kg CO2. Meanwhile, the calculation of Fuel Emission by using a motorized vehicle in the form of a car is 960 Kg CO2. Cost Reduction of efficiency in saving electrical energy consumption by 17%.